JHEA, Volume 14, n°1, 2016 - Full Issue - system, journal (Journal of Higher Education in Africa, 2021)
Contents Access to, and Success in, Higher Education in Post-apartheid South Africa: Social Justice Analysis Chika Sehoole and Kolawole Samuel Adeyemo ....................1 Revisiting the Postmodern Condition of a Higher Education Landscape: South Africa’s Higher Education Epochal Archive, 1999–2002 Chaka Chaka & Mashudu Churchill Mashige .......................19 A Decade of Biomedical Research in West Africa (2005–14): A Bibliometric Analysis of the Ten Most Productive Countries in MEDLINE Williams Ezinwa Nwagwu ......................43 A Review of Academic Freedom in Africa through the Prism of the UNESCO 1997 Recommendation Kwadwo Appiagyei-Atua, Klaus Beiter & Terence Karran..................85 Reconnecting the University to Society: The Role of Knowledge as Public Good in South African Higher Education Michael Cross and Amasa Ndofirepi .............................119 Availability of Study Time for Undergraduate Finance Students at an Open and Distance Learning Institution in South Africa C.F. Erasmus and G.P.M. Grebe .........................141 Towards the Institutionalization of Research Uptake Management in Sub-Saharan African Universities Sara S. Grobbelaar and Tomas Harber ............................155